Metal bioaccumulation in edible target tissues of mullet (Mugil liza) from a tropical bay in Southeastern Brazil - Hauser-Davis, Rachel Ann; Bordon, Isabella C.A.C. [UNESP]; Oliveira, Terezinha F.; Ziolli, Roberta Lourenço (Elsevier, 2016)
The present study aimed to investigate metal bioaccumulation in mullet (M. liza) from a tropical bay located in Southeastern Brazil, comparing a previously considered reference site to a known contaminated area of the bay, as well as to conduct human health risk assessments with regard to the consumption of this species. The metal concentrations were compared to the maximum residue level (MRL) in foods established by the different national and international regulatory agencies, and the Provisional Tolerable Daily Intake (PTDI) was determined and compared to reference values. Chromium (Cr), Zinc (Zn), Copper (Cu), Manganese (Mn), Nickel (Ni), Cadmium (Cd) and Lead (Pb) concentrations were determined in the gills, muscle and liver of 28 mullet by ICP-MS after acid digestion. Certain metals exceeded MRL guidelines established by different regulatory agencies, indicating human health risks associated to these metals. PTDI values, however, did not exceed corresponding metal values proposed by the World Health Organization. The metal concentrations found in the mullet samples indicate that the previously considered reference site is now showing signs of anthropogenic contamination.
Keywords: Environmental monitoring; Human risk assessment; Metals; Mullet; Southeastern Brazil; Tropical bay